The level of indebtedness of communes in the area of Ostrołęka-Siedlce subregion - Wakuła, Monika (Management and Administration Journal, 2019)
Units of territorial government have limited financial possibilities to carry out tasks.If they want to meet the demands of the local community and to improve the level of attractivenessof the area occupied by them, they have to use repayable sources of financing. In order to protectthemselves from a liquidity crisis, units should analyze their financial situation very carefully andevaluate financial safety while making decisions. Incurring debts by local governments is regulatedmainly by the law. A legislator introduced various limits concerning running up a debt in generallyapplicable regulations. The Public Finance Act of 2009 changed the regulations. An individual debtratio for local government units was introduced. The new limit came into effect in 2014. The aim ofthe article is an attempt to present legal conditions influencing debt management of a communeand the analysis of financial results based on the conditions as well as the level of indebtedness oflocal governments of communes between 2009 and 2014. The elaboration indicates causes,sources and directions of using repayable sources of financing on a given area. The article usesconventional research methods, i.e. the analysis of the subject literature, legal acts and comparativeanalysis of the level of basic budgetary categories influencing the level of commune indebtedness.The comparison was carried out on communes in Poland, the Mazovia province and thesubregion of Ostrołęka-Siedlce with the division into rural, urban and urban-rural communes.